Immobilization of phosphotungstic acid (PTA) on imidazole functionalized silica: evidence for the nature of PTA binding by solid state NMR and reaction studies - Sofia, L. T. Aany; Krishnan, Asha; Sankar, M.; Raj, N. K. Kala; Manikandan, Palanichamy; Rajamohanan, P. R.; Ajithkumar, Thalasseril G. (Journal of Physical Chemistry C, 2009)
Phosphotungstic acid (PTA) immobilized onto imidazole functionalized fumed silica and was used its an efficient catalyst for epoxidation of a variety of olefins using aqueous H(2)O(2) as all oxidant. Negligible leaching of PTA under the reaction conditions employed indicates a strong interaction between PTA and imidazole The immobilized catalysts Could be separated and reused after the catalytic cycle Evidence for the heterogenization of PTA oil the imidazole functionalized fumed silica has been inferred from different spectroscopic techniques like IR, UV-vis, and NMR. Importantly, the nature of binding of PTA oil the support has been studied in detail by solid state NMR spectroscopy using (15)N labeled imidazole Support. It is clear from the NMR Studies that the effective heterogenization of PTA is mainly due to imidazolium ion Formation oil the support by the acidic protons of PTA and the resultant ion pair